Necessity in international law - Ohlin, Jens David; May, Larry (New York, NY : Oxford University Press, 2016)
This title aims to trace the various uses of the concept of necessity in international law, with the goal of determining whether there is any overarching unity to these uses across the subdisciplines of international law. The authors not only discuss necessity in international humanitarian law and jus in bello, but also aim to situate necessity as understood in IHL within a larger discourse of international law generally, and to untangle the confusing and often inconsistent usages of the term 'necessity' in these broad areas of international law, including human rights law. The authors argue that the concept of necessity in international law has three different conceptions that cut across the various domains of international law: necessity as exception, necessity as license, and necessity as regulation.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 9, 2016).
Keywords: War (International law); Necessity (International law); Military necessity; Law; International law